A relação entre o nível de gastos socioambientais voluntários e a obtenção de benefícios fiscais - Oliveira, Edimundo Dias de (2013)
Volunteer expenses with the Environment is becoming, every time more, regular action in various companies. Involvement and propagation practices, also policies aimed for corporate sustainability, can be considered common today, counting even with standard reports that provide some descriptive elements about these practices. There is, however, a gap in the scientific literature about the relevance of such participation spending on business structure. Many companies indicate in their reports the existence of social and environmental costs, but the real impact of these actions are unclear, beyond the supposed improvement of the institutional image. This exploratory, qualitative approach, aimed to verify if the level of corporate environmental spending is associated significantly with the tax benefits that they may have. The sample consisted of 35 companies of the Índice de Sustentabilidade Empresarial (ISE) of BM&F Bovespa . The techniques that were applied are the content analysis. The results showed that the average level of environmental expenses are higher than the tax benefits obtained, indicating that these companies used a combination of donations, sponsorships and investments, suggesting the existence of other factors beyond the tax benefits limits involved.